TiO2 nanoparticle size dependence of porosity, adsorption and catalytic activity - Zaki, Mohamed I.; Fouad, Nasr E.; Mekhemer, Gamal A. H.; Jagadale, Tushar C.; Ogale, Satishchandra B. (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2011)
The issue of size-sensitivity of the surface properties of anatase TiO2 is addressed by examining three samples synthesized by aqueous sol-gel method having different particle sizes on the nanoscale (8-19 nm). A number of characterization methods, namely, X-ray powder diffractometry, infrared spectroscopy, UV-vis diffuse reflectance spectroscopy, sorptiometry and electron microscopy are employed. The data obtained reveal interrelated dependencies of the surface area, porosity, nitrogen and pyridine adsorption capacity and strength, and catalytic methylbutynol decomposition activity on the size of titania nanoparticles. Pertinent size-dependent bulk properties are also revealed and used to account for the changes conceded by the surface properties. Accordingly, going from 19 to 8-nm sized titania particles has been found to stabilize the anatase structure, weaken the surface acidity, and blueshift the UV absorption edge of titania. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Catalytic methylbutynol decomposition activity; Nano-titania; Particle size dependencies; Pyridine sorptiometry; Surface texture